A Direct Assessment of the External Domain of Food Environments in the National Capital Region of India - Chaudhry, Monica; Jaacks, Lindsay M.; Bansal, Monu; Mahajan, Palak; Singh, Ayushi; Khandelwal, Shweta (Frontiers in Sustainable Food Systems, 2021)
Data on food environments in India and other low- and middle-income countries are scarce. The objective of this study was to assess the four dimensions of the external domain of food environments (availability, price, vendor and product properties, and marketing) in food establishments in the National Capital Region of India. The assessment focused on fruits, vegetables, and ultra-processed foods. The 60 food establishments surveyed were categorized as stores, restaurants, or mobile food vendors. Only 13.3% of food establishments sold fruits and vegetables. Stores were more likely to sell vegetables than mobile food vendors (14.8% versus 6.2%, respectively) and sold a greater variety of both fruits and vegetables as compared to mobile food vendors (mean [SD] of 8.6 (3.2) fruits and 18.6 (9.2) vegetables available at stores versus 5.5 (5.7) fruits and 25 vegetables available at the one mobile food vendor who sold vegetables. However, these healthy food items were more expensive at stores. The availability (100% of stores, 12.5% of mobile food vendors, and 12.5% of restaurants) and variety (156 types) of ultra-processed foods across food establishments were higher than fruits and vegetables. A greater percentage of food establishments displayed advertisements for ultra-processed foods as compared to unprocessed or minimally processed foods such as fruits and vegetables. The National Capital Region of India has an unhealthy food environment. Regulations that limit the availability of ultra-processed foods and improve the availability and affordability of fruits and vegetables are needed to reverse the rising tide of chronic non-communicable diseases in this setting.